PENGGUNAAN GRAMATIKA DALAM WACANA POLITIK: STUDI REPRESENTASI BAHASA SEBAGAI SISTEM MAKNA SOSIAL DAN POLITIK - Santoso, Anang (Diksi, 2015)
The grammar of the Indonesian language is greatly made use of in political discourse and especially after the era of the Old Order. Via grammatical forms, the political elite fights for its power and ideology, both explicitly and implicitly, causing an unbalanced political communication. A research study this article is about was conducted to (1) describe and interpret the utilization of grammaticality in political discourse and (2) clarify why certain grammatical forms are paid special attention while others are not. The study applied a critical qualitative approach with a "critical discourse analysis" design from Fairclough (1989: 1995). In this perspective, no text produced by the political elite is neutral from political interest. Discourse is a social construction and results from social-historical and political conditions. There is no discourse which is a social vacuum. Discourse is a social creation reflecting the interests of certain social groups. The research results indicate that (1) each group of the Indonesian political elite uses transitivity with material meaning, agent nominalization, the passive voice, and the negative form to show its power and hide its ideological position, (2) each assumes the role of information provider, shows its authority in the presence of the other groups and the Indonesian society, and asserts its power by choosing to use the personal pronouns we and I, (3) it makes considerable use of modality expressing authority, and (4) there are institutional and cultural processes explaining why certain grammatical forms are paid special attention while others are not. Keywords: grammaticality, political discourse